The Influence of Social Media on the Formation of Public Opinion in the State Policy Making Process - Rahmania Nur Hariani; Dodi Jaya Wardana (Law Development Journal, 2025)
Modern life today is inseparable from information technology, one of which is the use of social media, where everyone can access various things they want to know. Social media is used to facilitate daily life, especially in terms of accessing information such as socio-political and economic. Along with the rapid development of information technology, social media has become a powerful platform for sharing information, interacting, and seeking public support. This phenomenon raises important questions about how social media shapes public opinion and, ultimately, influences the political process and policymaking. With social media, anyone can increase or show one's popularity and can also create narratives that are less accurate and objective about someone. Despite the various positive impacts of social media, it also has negative impacts. If users are unable to properly filter news or information containing divisions, hoaxes or fake news, issues of ethnicity, religion, and others carried out by irresponsible people, such information can cause chaos and can certainly divide unity. Therefore, the problem of this research is the level of influence of social media on public formation and what role social media plays in the formation of public opinion in the state policy process, whether constructive or critical. With the normative method, namely the normative legal research method (normative juridical), namely studying the legal rules, theories and principles that regulate freedom of opinion, the right to information and public participation in the process of forming state policy.